2010
DOI: 10.1590/s1806-37132010000600012
|View full text |Cite
|
Sign up to set email alerts
|

Envelhecimento pulmonar acelerado em pacientes com obesidade mórbida

Abstract: Lung age is increased in patients with morbid obesity, suggesting premature damage and accelerated lung aging, as evidenced by the discrepancy between chronological age and lung age. The determination of lung age might become a new tool for understanding pulmonary function results, for patients as well as for health professionals, in relation to obesity control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…In a study aimed at evaluating the harm obesity can cause to lung function, Melo et al 22 found significant differences in FVC and FEV 1 between the obese and normal weight groups. The authors demonstrated pulmonary damage through the concept of lung age and found that this measure increases in patients with morbid obesity, suggesting early damage and accelerated lung aging in these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In a study aimed at evaluating the harm obesity can cause to lung function, Melo et al 22 found significant differences in FVC and FEV 1 between the obese and normal weight groups. The authors demonstrated pulmonary damage through the concept of lung age and found that this measure increases in patients with morbid obesity, suggesting early damage and accelerated lung aging in these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…They understand that the diagnostic tool was comparable to the classical one and can be used in daily practice. Melo et al110 determined the lung age of patients with morbid obesity and compared it with the chronological age of these patients, emphasizing the premature damage that morbid obesity does to the lungs. Pereira et al111 evaluated the efficacy and safety of two inhalers for Mometasone furoate administration in patients with asthma and find that the use of the single-dose inhaler developed in Brazil is as effective and safe as is that of a standard inhaler in the treatment of patients with asthma.…”
Section: Introductionmentioning
confidence: 99%
“…[248][249][250] Lung age was significantly older in patients with morbid obesity, severe airflow limitation, and COPD. [248][249][250][251]…”
Section: Lung Agementioning
confidence: 99%